Mature results of the M. D. Anderson Cancer Center risk-adapted transplantation strategy in mantle cell lymphoma - Tam, Constantine S; Bassett, Roland; Ledesma, Celina; Korbling, Martin; Alousi, Amin; Hosing, Chitra; Kebraei, Partow; Harrell, Robyn; Rondon, Gabriela; Giralt, Sergio A; Anderlini, Paolo; Popat, Uday; et al. (Blood, 2009)
In this study, we analyzed the long-term outcome of a risk-adapted transplantation strategy for mantle cell lymphoma in 121 patients enrolled in sequential transplantation protocols. Notable developments over the 17-year study period were the addition of rituximab to chemotherapy and preparative regimens and the advent of nonmyeloablative allogeneic stem cell transplantation (NST). In the autologous transplantation group (n = 86), rituximab resulted in a marked improvement in progression-free survival for patients who received a transplant in their first remission (where a plateau emerged at 3-8 years) but did not change the outcomes for patients who received a transplant beyond their first remission. In the NST group, composed entirely of patients who received a transplant beyond their first remission, durable remissions also emerged in progression-free survival at 5 to 9 years. The major determinants of disease control after NST were the use of a peripheral blood stem cell graft and donor chimerism of at least 95%, whereas the major determinant of death was immunosuppression for chronic graft-versus-host disease. Our results show that long-term disease-free survival in mantle cell lymphoma is possible after rituximab-containing autologous transplantation for patients in first remission and after NST for patients with relapsed or refractory disease.